The role of the metabolome and non-coding RNA on pheochromocytomas and paragangliomas: an update - Bouça, Bruno (2022)
Pheochromocytoma and paragangliomas (PPGL) are rare neuroendocrine tumors. In some patients they exhibit malignant behavior characterized by the presence of metastases, limiting treatment options and survival rates. Therapeutic options are limited to surgery, localized radiotherapy, and a few systemic therapies. However, in several recent studies, non-coding RNA molecules are gaining increasing attention as markers of malignancy for PPGL. The understanding of PPGL development molecular mechanisms has improved in the last years, with some of the epigenetic regulatory mechanisms such as DNA and histones methylation, being better understood than RNA-based mechanisms. Metabolome deregulation in PPGL, with increased synthesis of molecules that facilitated tumor growth, results from the activation of hypoxia signaling pathways, affecting tumorigenesis. In addition, the assessment of these metabolites can be useful for the management of these tumors. This review summarizes recent discoveries linking metabolome and non-coding RNA to PPGL and their relevance for diagnosis and therapeutics.